Food choice factors affecting Malaysian green food consumption - Abdul Rahim @ Abdul Wahab, Husniyah; Md Jusoh, Zuroni; Lidew, Lidiana; Sulaiman, Norhasmah; Abu Bakar, Elistina; Jamaluddin, Askiah (Australian Academy of Business and Social Sciences, 2015)
In concurrent with the world development, the market and consumers experience the impact that changes their consumption pattern. As food is the basic need for all living creatures, wiseful choice is necessary to sustain healthy life. Nowadays, people are more aware and concerned with their food consumption and tend to opt for green food. Hence, this study was performed to identify the influence of factors on green food choice. The selection of food by consumers was based on Food Choice Questionnaire (FCQ) consisting of nine factors namely sensory appeal, natural content, health, ethical concern, weight control, convenience, familiarity, mood and price. The study was conducted on 600 adult respondents selected through simple random sampling based on areas in Klang Valley. The extent of influence from factors affecting green food choice was determined using multiple regression controlled with socioeconomic characteristic. Apart from the FCQ factors, green food knowledge and attitude were also identified their strength of influence on green food choice. Familiarity (B=.299; p=.001) and weight-control (B=-.269; p=.012) were the only FCQ factors that was found to be significantly affecting green food choice. Attitude towards green food consumption (B=.499; p=.000) and household income (B=.974; p=0.017) were also significant in influencing green food choice. More aggressive promotion on green food must take place towards healthy living.